Recycling of Spent Lithium-Ion Batteries Processing Methods and Environmental Impacts - An, Liang (Springer International Publishing : Imprint: Springer, 2019)
This book presents a state-of-the-art review of recent advances in the recycling of spent lithium-ion batteries. The topics covered include: introduction to the structure of lithium-ion batteries; development of battery-powered electric vehicles; potential environmental impact of spent lithium-ion batteries; pretreatment of spent lithium-ion batteries for recycling processing; pyrometallurgical processing for recycling spent lithium-ion batteries; hydrometallurgical processing for recycling spent lithium-ion batteries; direct processing for recycling spent lithium-ion batteries; high value-added products from recycling of spent lithium-ion batteries; and effects of recycling of spent lithium-ion batteries on environmental burdens. The book provides an essential reference resource for professors, researchers, and policymakers in academia, industry, and government around the globe.